Pemanfaatan Tandan Kosong Sawit Dan Rumput Sebagai Bahan Kompos di PT Bukit Asam, Sumatera Selatan - Arief Juniarto; Irdika Mansur; Arief Sabdo Yuwono (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2018)
PT Bukit Asam had strategies to improve soil fertility in the ex-mine land using compost. The amount of compost added to the soil depend on the extent of reclamation area. Oil palm empty fruit bunch and grass are highly potential to be used as the compost materials in reclamation area. The objectives of the research were to characterize the compost from oil palm empty fruit bunch and grass, and to compare the suitability between the result of this research and nasional standard compost. Oil palm empty fruit bunch and grass were obtained from PT Bumi Sawindo Permai and reclamation area of PT Bukit Asam, respectively. Composting site was located in the ex-mine land of PT Bukit Asam. Composting method used passively aerated static pile system. The results showed that the compost characteristic of oil palm empty fruit bunch compost had a dark yellowish brown color, pH at 9.3, C/N ratio at 14, and nutrients (C-Organic, N, P, K, and Mn Total). The compost characteristics of grass had a very dark brown, pH at 7.3, C/N ratio at 7, and nutrients (C-Organic, N, P, K, and Mn Total). The compost from oil palm empty fruit bunch and grass were in accordance with the national standard of compost.Keywords: empty fruit bunch, grass, compos